Kajian Efek Stimulan Dari Beberapa Minuman Energi Kemasan Sachet Yang Beredar Di Pasaran - Zet Rizal; Candra Syuryani; Helmi Arifin (Jurnal Farmasi Higea, 2013)
A research of some sachet energy drinks on the market on the activity of the central nervous system stimulant for white mice (Mus musculus, L.) has been done. The samples labelled Minuman Energi Sachet MES 1, MES 2, MES 3, MES 4 and MES 5 and administered perorally. Parameters used for stimulant activity were endurance tested using Rotary road, while  motoric activity and curiosity tested using Automatic Hole Board. Each sample has administration volume of 0.52 ml/20 g BW. Comparator ued is caffeine 0.13 mg/ 20 g BW. From the research that has been done, it is known that MES 1, MES 2, MES 3, MES 4 and MES 5 has a central nervous system stimulant activity by increasing endurance, motoric activity and curiosity in mice significantly.